The development of the chondrocranium of Merluccius capensis Cast. and its possible contribution to the distributional ecology of the Cape hakes - Badenhorst, A.(Abraham) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1984.